PERANCANGAN DAN IMPLEMENTASI JARINGAN FTTH GPON DI CLUSTER GILIMANUK - Mahardika Adnyana, Kadek Dwi; Diafari Djuni, IGAK; Esta Dewi Wirastuti, NMA (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUM, 2024)
This research aims to meet the target of building a homepass network of 512 homepasses from PT. PLN ICON PLUS in the North Bali UP3 area sector, namely the Gilimanuk Village area, Melaya District, Jembrana and the use of Huawei Optical Line Terminal (OLT) equipment with a total of 8 ports as well as the use of backbone network access that is already available in the Gilimanuk area. Gilimanuk demographically has an area of 56.01 km2 and consists of residential buildings inhabited by 2,451 families. To accommodate homepass from the Gilimanuk housing complex, this research offers a cascading scheme for Fiber To The Home (FTTH) with Gigabit Passive Optical Network (GPON) technology that is appropriate to use but still pays attention to the quality of the network provided. In determining the feasibility of the network design and determining the appropriate cascading scheme for the Gilimanuk Cluster, the parameters in network design and implementation are focused on measuring the power link budget in theory and implementation, then the rise time budget value in the network optisystem software simulation. The results of this research show that the 1:4 to 1:16 cascading scheme has better FTTH network system feasibility than the 1:8 to 1:8 cascading scheme with a Prx value of -18.42 dBm, which does not exceed the minimum Prx threshold value of the ITU-T G standard. 984, namely -28 dBm, then the rise time budget shows the system rise time value: 0.25537 ns, which does not exceed the maximum rise time limit, namely 0.292 ns, so the 1:4 to 1:16 cascading scheme is feasible to implement.